RESPOSTAS ESTRATÉGICAS NA GESTÃO DE RISCOS NA AGRICULTURA : UM ESTUDO NO NÚCLEO REGIONAL DE PRODUÇÃO DE SOJA DE IRATI - SIATKOWSKI, ALDO (2022)
With the population increase predicted by the UN of more than two billion people in the world, and the consequent need for an increase in food production of more than seventy percent, predicted by the FAO until 2050, studies on the forms of agricultural production are necessary. Brazil has an important global participation in agribusiness, being one of the main players in world supply, and with expressive representation in the segment's participation in the national economy, with about twenty-seven percent of the national Gross Domestic Product. However, agricultural activities are mostly carried out in the open, being subject to various types of production risks, but also exposed to risks of market volatility and business environment. In this context, this study aimed to understand how soybean producers in the regional center of Irati respond strategically in managing the risks inherent to their activity. Soybean is the main agricultural crop in Brazil, and in Paraná, and is intended for human and animal food. In order to respond to the research objectives, a survey was carried out with one hundred and thirty soybean producers from the regional nucleus of Irati, which comprises nine municipalities in Paraná, through the application of Survey questionnaires, containing eighty-two questions, divided into three categories of analysis, seeking to respond to objectives related to the Strategic Behavior of rural producers in the face of agricultural risks; Strategic Decisions against agricultural risks; and the types of Agricultural Risks faced by producers. The research was classified as descriptive, with a qualitative approach, having as a research method the field study and from the data collection statistical methods were carried out using the Kruskal-Wallis, Mann-Whitney, Spearman Correlation, Equality of Two Proportions, Confidence Interval for Mean and Box-Plot Graphs. The results showed that only 6.9% do not think about the risks involved in the operation, and more than half of those surveyed seek technical assistance in risk management. In relation to strategic behavior in the face of agricultural risks, producers behave more passively, acting out of habituality, imitation and agreement as risk management tactics, moving from more passive to more active tactics. Regarding strategic decisions, it can be seen that soybean producers in the regional center of Irati use three forms of decisions, and the highest average perception is that mitigating risks is more important, using strategies in anticipation of possible risks. One of the challenges by the research correlations is one of the ways in which producers mitigate their production risks with the purchase of inputs with resources from financial institutions. It has also been shown that the strategy of transferring risks to third parties, even at a cost, is better than coping with post-causes. Regarding the different types of agricultural risks, it was found that producers have an average level of awareness of the three types of risks with a small average variation between the three types, and the highest average agreement was related to the risks of the business environment, followed by market risks and then production risks. Even considering that uncertainty and risks in the agricultural environment cannot be totally avoided, the results of the study lead us to think that instruments for improving awareness of the risks to which producers are exposed can be a strategy to improve results. As a theoretical contribution, the study brought a strategic approach applied to agribusiness. As a practical contribution, it presents an opportunity for agricultural policymakers, government, associations, academia, among others, to better understand the attitudes and risks of producers, providing them with greater knowledge about possible risks, as well as management tools for better results.